A Fiqh Muamalah Perspective on the Ratio Decidendi of Supreme Court Decision No. 155 K/Ag/2021 in Murabahah Dispute Resolution - Qoniatun Nadziroh; Norma Fitria (UIN Siber Syekh Nurjati Cirebon, 2026)
This study examines the resolution of a debt dispute arising from a murabahah contract in Supreme Court Decision No. 155 K/Ag/2021, which involved a customer and PT Bank Sumut’s Karya Sharia Sub Branch. The dispute arose due to a breach of contract in the execution of the murabahah contract and was subsequently resolved through the Religious Court system. The research issues examined include: (1) What was the ratio decidendi of the Supreme Court panel in resolving the debt dispute arising from a murabahah contract at PT Bank Sumut’s Karya Sharia Sub Branch in Supreme Court Decision No. 155/K/Ag/2021? and (2) What is the perspective of fiqh muamalah on the ratio decidendi of the Supreme Court panel in Case No. 155 K/Ag/2021 regarding the resolution of a debt dispute at the Syariah Karya Branch of Bank Sumut’s Karya Sharia Sub Branch This study employs normative legal research through statutory, conceptual, and case-based approaches. The legal sources used were Supreme Court Decision No. 155 K/Ag/2021, relevant laws and regulations, and literature on fiqh muamalah. The findings indicate that the Supreme Court identified errors in the application of the law by the trial and appellate courts, particularly in declaring the lawsuit premature, even though the case concerned the parties’ rights and obligations under the murabahah contract rather than the cancellation of the auction. The Supreme Court further emphasized that rulings on sharia economic disputes must apply the principles of Islamic law, specifically the principle of ta’awun (mutual assistance). Keywords: Murabahah Contract; Islamic Banking Disputes; Fiqh Muamalah; Ta’awun